PENGARUH PENYALURAN KREDIT USAHA RAKYAT (KUR) PT. BANK RAKYAT INDONESIA (PERSERO) TBK CABANG PEKANBARUTERHADAP TINGKAT PENDAPATAN INDUSTRI KECIL SEKTOR PERDAGANGAN DI KOTA PEKANBARU - Lukman Nul Hakim; Mardiana Mardiana; Rahmat Richard (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was conducted at Bank Rakyat Indonesia (Persero) Tbk Pekanbaru Branch. The purpose of this study is to find information about taxes and revenues for small sectors in Pekanbaru city before and after receiving the distribution of community business credit (KUR) PT. Bank Rakyat Indonesia (Persero) Tbk Pekanbaru Branch. The sample of this study were 99 people, the data were collected by questionnaire technique, and the analysis using Z-Test using SPSS version 21 assistance. The results showed that there was a significant factor in the small sector in Pekanbaru City before and after receiving the people's business credit (KUR) PT. Bank Rakyat Indonesia (Persero) Tbk Pekanbaru Branch zcount (5.197)> from ztable (0.1660) and sign. (2-tailed) 0,000 <0.05.Keywords : Revenue Rate